Fabrication of a test bed for performance testing of Unmanned Aerial Vehicle (UAV) propulsion system - Adib, Azmi (2013)
This project report has been conducted because of the Unmanned Aerial Vehicle (UAV) power plant development performance testing (static test) facilities is not fully deployed. The main purpose of this project is to fabricate a test bed for the UAV propulsion system. To test the capability of measuring aircraft performance namely thrust, available power, brake shaft power, propulsive efficiency, brake specific fuel consumption and thrust coefficient. In this study, the test bed model was designed to test the nitro engine Radio Control (RC) which is a model of Thunder Tiger PRO .36. The unknown value of parameters can be determined by reading the sensors. Some sketches software had been used such as Autocad and Solidwork to draft out the shape of the test bed. The fabrication process for this project must through a lot of process that must be followed step by step. This is to ensure that the design had been fabricated by following the design specification. From this experiment, the result shows that the fabricated test bed can be used to study the engine performance and performance parameters are directly proportional to the engine speed which mean the speed of the engine affects the increasing of the parameters. Some methods of improvement for the combination of test bed are also provided for further improvement of the test bed. As the conclusion, all the engine performance parameter can be calculated from the test bed.